Death of a gingerbread man - Hollis, Lee (Hollis, Lee. Hayley Powell food and cocktails mystery, 2024)
"With the holiday season in full swing, food and cocktails columnist and restauranteur Hayley Powell has lots to check off her last-minute to-do list. Not included is the sudden arrival of her father, who hasn't been in the picture since she believed in Santa Claus. Dwight Jordan's presence in Bar Harbor might just be the unwanted gift that keeps on giving--especially after he becomes the top suspect in a case of yuletide murder...As Hayley plans a New Year's Eve bash while handling a hefty helping of family drama, she must lean into her closest friends to unravel a twisted mystery. Because the countdown is on to find out who killed the sore loser at the gingerbread house contest before Dwight disappears again--this time behind bars. And the more Hayley learns about the possible culprits, the more she knows it's either crack the case ASAP or watch everything crumble like a stale cookie..."--